Human-Animal Relations in Shamanism Within Nordic Contexts - Joy, Francis; Armstrand, Peter; Russell-Møller, John (2024)
The subject matter of human-animal relations with regard to inter-species communication is a field of study that is rich and varied within northern and Arctic landscapes and discourses. This focus of attention comes from within the fields of shamanism, animism and cosmologies from various time periods with reference to the creation of sacred narratives, recorded through art and oral traditions. In this research, both animistic and narrative approaches are used to engage with these respective fields of inquiry through data collection and participant observation that links these important subject matters together. Firstly, through data collection from two prehistoric rock art landscapes in Finland, secondly, from data analysed from within cosmological landscapes within two sacred Sámi Noaidi drums from the seventeenth century Sweden, and lastly, through data collected via interviews with two contemporary shamans about their spiritual work, beliefs and practices which also includes knowledge sharing from a contemporary Sámi drum landscape. Collectively, these spheres can be understood as adjoining landscapes where past and present worlds meet. Rock art research as a foundation to the study provides some of the very early depictions of human-animal relations with regard to inter-species communication (telepathy) illustrated through art. From these sources, cosmologies have developed which are characterized by shamanic visionary narratives and coproduction of knowledge determined by engagement with various spiritual beings across millennia. Through an examination of these different types of behaviour, the results of the research demonstrate how it is possible to grasp in what ways they link past and present practices, beliefs and traditions together and why these are important.Keywords: rock art, sacred landscapes, human-animal communication, drum figures, narratives, telepathy. Título: Relaciones Humano-Animal en contextos nórdicosResumen: El tema de las relaciones humano-animal en cuanto a la comunicación entre ...